Kompetensi Sumber Daya Manusia Di Era Transformasi Industri 4.0 Dan Digital 5.0 Untuk Meningkatkan Produktivitas Kerja Karyawan - Idham Ikhsan; Enas Enas; Aini Kusniawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Competence in carrying out tasks, which are needed by aligning knowledge and expertise by communicating with developments in business and digital technology. as well as Competency training that suits the needs of the company as well as outreach to employees and outreach and training. Tool selling and monitoring the digital base are already aware of and have been executed in the field both in terms of product education and sales of digital products, have been socialized and understand Telkomsel's CSP 2023-2027. The research method that will be used in this research is a qualitative research method with a descriptive approach. The design used in this study is a case study design. The results of the research are 1. HR Competence in the Era of Industri 4.0 and Digital 5.0 Transformation to Increase Employee Work Productivity at PT Telkomsel Se-Priangan Timur, competency or capacity in carrying out tasks, in this case what is needed by aligning knowledge and expertise by communicating with technological developments business and digital. 2. Obstacles in HR Competence in the Era of Industri 4.0 and Digital 5.0 Transformation to Increase Employee Work Productivity At PT Telkomsel Se-Priangan Timur, not all Telkomsel employees already know Digital Culture in their daily work and mastery of existing Technology by the Network Department in New Mastery 5G Technology Network employees, HR who have high creativity are needed in the era of volatility, uncertainty, complexity, ambiguity (VUCA) to make Innovations that support Digital Business.3. Efforts in HR Competence in the Industri 4.0 and Digital 5.0 Transformation Era to Increase Employee Work Productivity at PT Telkomsel Se-Priangan Timur, Digital Culture training in daily work and mastery of existing Technology by the Network Department in Mastering New Technology 5G Network employees, trained HR those who have high creativity are needed in the era of volatility, uncertainty, complexity, ambiguity (VUCA) to make innovations that support Digital Business.